Knowledge Transfer, Innovation, Cultural Intelligence & Firm Performance Among German Mncs Subsidiary In Malaysia - Ooi, Zheng Yao (2023)
This study highlights the importance of knowledge transfer and innovation as fundamental sources of competitive advantage that improve the firm performance of subsidiaries of German multinational companies (MNCs) operating in Malaysia. The role of subsidiaries within the MNCs has changed from time to time. Foreign subsidiaries have benefited from innovation by generating new resources or owning assets that provide a competitive advantage to achieve targeted firm performance and successfully operate in specific locations. Following extant literature, innovation is studied in various forms, such as innovation in management, organization, marketing, and product, while knowledge transfer consists of codified versus personalized knowledge transfer. More importantly, the direction and strength of these relationships are tested using cultural intelligence as a moderating variable. In this research study, the non-probability sampling method and purposive sampling technique are applied to analyze the data, and the firm or organization is considered the unit of analysis. Using structural equation modeling in SPSS-AMOS and descriptive statistics in Microsoft Excel, this paper empirically tests the relationships between knowledge transfer, innovation, and firm performance as mediated by competitive advantage and moderated by cultural intelligence. The findings support the proposed hypotheses as applied to subsidiaries of German MNCs in the manufacturing xvii industry in Malaysia.